Comparing the performance of low-grade nickel ore and limestone for treatment of synthetic acid mine drainage - Turingan, Casey Oliver A. (Animo Repository, 2020)
Goethite is a dominant component of nickel laterite ores, which is capable of adsorbing metal ions in water. The potential of the unused low-grade nickel ore (LGO) to treat synthetic acid mine drainage (AMD) was investigated. LGO characterization identified the presence of goethite (α-FeOOH), calcium oxide (CaO), and manganese aluminum oxide. The performance of LGO for AMD treatment was evaluated using jar test and compared with limestone. At 0.5 ml AMD/g media, LGO increased the pH of AMD to 5.36 while limestone completely neutralized it. LGO removed more than 99% of Al and Fe, 94% of Ni, and 93% of sulfates compared to a 70% sulfate removal using limestone. The lower sulfate removal may be due to the armouring of the limestone surface. Furthermore, a batch test was conducted using both LGO and limestone as layered treatment media in an oxic and anoxic setup. Effluent pH remained constant while conductivity and TDS stabilize at 2,000 μS/cm and 1,000 ppm, respectively. Both setups achieved 99% removal of Fe and Al, ~90% Ni removal, and between 70% and 80% sulfate removal. These results indicate that LGO is a possible alternative material to be used for heavy metal adsorption for AMD treatment. © 2020 Curtin University and John Wiley & Sons, Ltd.